A novel approach to identifying mantle-equilibrated zircon by using trace element chemistry ... - Ni, Ziqin; Arevalo, Ricardo; Piccoli, Philip; Reno, Barry (Interdisciplinary Earth Data Alliance (IEDA), 2020)
Zircon U–Pb isotope data were collected on zircon separates, embedded in 2 cm epoxy blocks, by laser ablation inductively coupled plasma mass spectrometry (LA–ICP–MS) at the Geological Survey of Denmark and Greenland (GEUS) following the methods of Frei and Gerdes (2009) and Frei et al. (2006), and using analytical conditions described in detail in Dyck et al. (2015). A New Wave Research UP213 frequency-quintupled solid state Nd:YAG laser system, employing a two-volume cell technology, was coupled to a Thermo-Fisher Scientific ELEMENT 2 double-focusing single-collector magnetic sector-field ICP–MS. Mass resolution was 300. U–Pb isotope data in zircon were acquired from single spot analysis using a spot diameter of 25 µm at a repetition rate of 10 Hz and a nominal laser fluence of 15–16 J/cm2. Trace element compositions in zircon were performed using a 40 µm spot diameter at a repetition rate of 10 Hz with 60% energy and a nominal laser fluence of ~6 J/cm2. Trace element analysis locations and U–Pb analysis ... : Ni, Z. Arevalo, R. J., Piccoli, P., Reno B., A novel approach to identifying mantle-equilibrated zircon by using trace element chemistry, Geochemistry, Geophysics, Geosystems (in review) ...